Indigenous Theatre Protocols - Sioui Durand, Yves (Percées)

(untitled) (Société québécoise d'études théâtrales (SQET), 2023)
How can existing and reimagined protocols contribute to the decolonization of performing arts practices among Indigenous artists? How can they allow us to reconnect with our languages and the pre-Columbian concepts they keep alive? Who we are and who we will be have not been captured by how we have been represented. Like all the peoples of the earth, we have our own theatre traditions. How can we repatriate or draw inspiration from non-Western forms of theatricality rooted in our ancient cultures? Artistic protocols are the walking sticks that might guide us towards discoveries and rediscoveries deeply rooted in who we truly are. They promise to lead us towards vital theatrical practices in an era in which ecological collapse threatens the future of humanity.